Pravne razsežnosti prepovedi nadlegovanja - Maučec, Gregor (Law & Society, 2013)
Book, written in Slovene, discusses the legal content and scope of the concept of discriminatory harassment, which is deemed to be an unlawful discrimination under modern EU non-discrimination law, in the context of implementation of provisions of relevant EU directives in legal systems of the United Kingdom and Ireland. the two most important EU non-discrimination directives, adopted under Article 13 of the Treaty Establishing the European Community (now Article 19 of the treaty on the Functioning of the European union) - Racial Equality Directive (Directive 2000/43/EC) and Employment Framework Directive (Directive 2000/78/EC) - explicity mention harassment as prohibited form of discrimination. Legal definitions contained in these two directives define harassment as discriminationdiscrimination itself. Prior to the transposition of the EU non-discrimination directives into their laws, while few member states tackled this issue either within the context of the law on equal treatment (e.g. Denmark, the United Kingdom and Ireland) or outside this context (e.g. France), that is in the framework of criminal, civil, health and safety or employment legislation. As a result of the implementation of relevant provisions of the two main non-discrimination directives (Directives 200/43/EC and 200/78/EC) a definition of harassment has been included in legislations of all EU member states. In most member states such legislative definition is a literal copy of the definition of harrasment that can be found in the Directives 2000/43/EC and 2000/78/EC. The approach to the definition of harassment that appears to be the most "generous" from the perspective of victims of discriminatory harrasment is the one that was taken by British legislator. Such legal position in respect of the prohibition of discrimination has been developed in British case law and is based on the extensive interpretation of non-discrimination laws.